Anisotropic two-dimensional electron gas at SrTiO(3)(110) - Wang, Zhiming (National Academy of Sciences, 2014)
Two-dimensional electron gases (2DEGs) at oxide heterostructures are attracting considerable attention, as these might one day substitute conventional semiconductors at least for some functionalities. Here we present a minimal setup for such a 2DEG––the SrTiO(3)(110)-(4 × 1) surface, natively terminated with one monolayer of tetrahedrally coordinated titania. Oxygen vacancies induced by synchrotron radiation migrate underneath this overlayer; this leads to a confining potential and electron doping such that a 2DEG develops. Our angle-resolved photoemission spectroscopy and theoretical results show that confinement along (110) is strikingly different from the (001) crystal orientation. In particular, the quantized subbands show a surprising “semiheavy” band, in contrast with the analog in the bulk, and a high electronic anisotropy. This anisotropy and even the effective mass of the (110) 2DEG is tunable by doping, offering a high flexibility to engineer the properties of this system.